Leaching of a copper flotation concentrate with ammonium persulfate in an autoclave system - Turan, M. Deniz; Altundogan, H. Soner (Springer, 2014)
The leaching behavior of a copper flotation concentrate was investigated using ammonium persulfate (APS) in an autoclave system. The decomposition products of APS, active oxygen, and acidic medium were used to extract metals from the concentrate. Leaching experiments were performed to compare the availability of APS as an oxidizing agent for leaching of the concentrate under atmospheric conditions and in an autoclave system. Leaching temperature and APS concentration were found to be important parameters in both leaching systems. Atmospheric leaching studies showed that the metal extractions increased with the increase in APS concentration and temperature (up to 333 K). A similar tendency was determined in the autoclave studies up to 423 K. It was also determined that the metal extractions decreased at temperatures above 423 K due to the passivation of the particle surface by molten elemental sulfur. The results showed that higher copper extractions could be achieved using an autoclave system.
Keywords: copper; concentrates; leaching; ammonium persulfate; autoclave